Assessment of General Populations Knowledge, Attitude, and Perceptions Toward the Coronavirus Disease (COVID-19): A Cross-Sectional Study From Pakistan - Khattak, Saadullah; Khan, Maqbool; Usman, Tahir; Ali, Johar; Wu, Dong-Xing; Jahangir, Muhammad; Haleem, Kashif; Muhammad, Pir; Rauf, Mohd Ahmar; Saddique, Kamran; Khan, Nazeer Hussain; Li, Tao; et al. (Frontiers in Medicine, 2021)
World Health Organization (WHO) recognized Coronavirus disease 2019 (COVID-19) as a pandemic in early 2021. The knowledge, attitudes, and perceptions of the public are critical for the development and effective implementation of SOPs to contain the contagion and minimize the losses. Thus, to understand and evaluate the knowledge, attitude, perceptions, and anxiety of Pakistani people towards the COVID-19 pandemic, this cross-sectional study, using an online survey, was designed. Multiple statistical tests including descriptive statistics, independent sample t-test, and one-way ANOVA were used to analyze the participants' demographic characteristics (frequency, percentage, mean and standard deviation). The results of the study indicated that seven hundred thirty-four participants took part in this survey. The gender, marital status, education, and residence showed a significant association with the knowledge score. The majority of the participants (95.4% and 96.7%) were of the view that the virus may be more dangerous for the elderly and in comorbid patients, respectively. Around half of the participants (52.5%) showed their concern that either they or their family members might get the infection. More than 98 percent of the participants held that COVID-19 would be successfully controlled in Pakistan by following the SOPs such as, frequently washing hands with soap and avoiding shaking hands, gatherings, and crowds. A vast majority of the participants showed disturbed thinking i.e. 89.0% of participants responded that they could not stop thinking about the coronavirus. Moreover, 82.3% of the participants felt frozen when they thought about or were exposed to horrific information about the coronavirus. The results in this study showed that Pakistanis had good awareness and reasonable attitudes and practices toward the full features of the COVID-19 pandemic. In the last, we suggest that mass-level education and propaganda are necessary for developing countries to improve and limit the gap between KAP towards COVID-19.